P127 A combined EEG and alpha tACS study on visual working memory in healthy ageing. Issue 3 (March 2017) - Grande, G.; Golemme, M.; Tatti, E.; Chiesa, S.; Velzen, J. Van; Bernardi Luft, C. Di; Cappelletti, M.
Abstract : Visual working Memory abilities (VWM) are known to diminish in healthy ageing (Brockmole et al., 2013), but the nature of this deterioration is still not well understood. A recent line of research has suggested that an impaired top-down suppression of irrelevant information (i.e. inhibitory abilities) might explain this decline (Gazzaley et al., 2005, 2007). Electrophysiologically, impoverished inhibitory abilities have been linked to alpha band oscillations (8–12 Hz, Klimesch et al., 2007), which is also known to be diminished in elderly (Ho et al., 2012). This therefore suggests a possible causal link between alpha oscillations and age-related VWM abilities difficulties. In this study, we sought to provide behavioural evidence of the causal role of alpha power oscillations in supporting inhibitory control in VWM. Specifically, using Alpha-power brain stimulation (tACS) we tested: (1) behaviourally, whether inhibitory abilities can be ameliorated in ageing, and (2) electrophysiologically (with EEG) the duration of any alpha-tACS after effects. Methods: Nineteen healthy ageing participants were tested on two different days with a VWM retro-cueing paradigm (Yoni et al., 2009) which assesses VWM precision and the ability to ignore task-irrelevant stimuli. The retro-cueing task was coupled with EEG before and after participants received either 10 Hz parietal (P3 and P4) alpha-tACS or sham (in different sessions counterbalanced across all participants) while performing the same task. Results: Relative to sham, Alpha-tACS modulated participants' ability to ignore task-irrelevant stimuli, an improvement maintained for 6–10 min during the following EEG recording. This change corresponded to a significant positive correlation with the absolute amplitude of the N200 peak recorded at a left parietal site (P3). Conclusions: Inhibitory control abilities in VWM are causally linked to alpha frequency in healthy ageing participants who become better at suppressing task-irrelevant stimuli following Alpha-tACS0. The improved performance positively correlated with the absolute amplitude of N2 component at the P3. This effect may correspond to increased attentional resources directed to a stimulus, due to Alpha inhibiting the allocation of attentional resources to distracting stimuli.